Effect of Surgeon Volume on the Results of Surgical Treatment of Pediatric Trigger Thumb - Korte, Johanna (My University, 2025)
Objectives Release of pediatric trigger thumb is the most common elective hand procedure in children. Insufficient release of the tendon sheath may lead to recurrence or reoperation. Methods We retrospectively analyzed the results of surgical treatment of 55 patients (60 thumbs) that had undergone surgical release for pediatric trigger thumb. The operating surgeons were divided into low-volume (LV, less than 5 procedures during the follow-up period) and high-volume (HV, more than 5 procedures) surgeons. Results LV surgeons operated on 28 patients and HV surgeons operated on 27 patients. The most common complication was postoperative infection in 4 % (2/55) of cases. One patient operated by a LV surgeon required resurgery due to an extension deficit of the thumb. Conclusions: Surgery for pediatric trigger finger is safe with low rate of complications. Higher per surgeon volume may help to reduce resurgery.
Keywords: trigger digit, trigger thumb, child, congenital, surgery